Effect of chemical treatment on mechanical properties of fiber reinforced composites. (2022) - Lakshmi Narayana, S.; Lakshmi Narasimhamu, K.; Anantha Krishna, N.; Vishnu Vardhana Naidu, B.; Deekshith, C.
Abstract: Reuse, recycling and disposal are the important aspects of present day application of material used for construction of buildings, machines or any other domestic appliances, etc.For various environmental considerations, the use of sustainable, eco friendly or green concepts have become mandatory in the development of any technology for process or material. This work is focused on development of natural fiber composites and their products using the fibers of Thespesia Lampas and Hibiscus Cannabinus plants. These fibers long and soft and are very much in use in the domestic sector for various products. Laminates are made using these fibers and general purpose isopthalic resin. Tensile, flexural and Water Absorption tests are conducted to evaluate the properties. Unidirectional and cross woven mats are used for making the laminates, the mats are also coated with poly vinyl alcohol to study its effect on various properties. In each case of the laminate, the fibers are considered with treatment of NaOH also to find the consequence of treatment on the properties.